The Effects of Experimental Marketing and Experiential Value on Customer Loyalty with the mediation of Customer Satisfaction - Adha, Abdul Fuad Amirul; Puspaningrum, Astrid; Rahayu, Mintarti (Devotion : Journal of Research and Community Service, 2023)
This research focuses on the role of Experiential Marketing and Experiential Value in increasing Customer Loyalty through Customer Satisfaction in consumers of Santri Farm Kudus. The purpose of this study is to explain and analyze the effect of Experiental Marketing and Experiential Value on Customer Loyalty both directly and indirectly through Customer Satisfaction mediation. This type of research is explanatory research with a quantitative approach. The population in this study were consumers who had enjoyed and purchases Santri Farm products. Data was collected by distributing questionnaires to 160 respondents who met the criteria. Data analysis used Structural Equation Modelling Partial Least Square (SEM-PLS) with Smart PLS Software. The results of this study show that Experiential Marketing has no significant effect on Customer Loyalty. Experiential Value has a significant effect on Customer Loyalty. Customer satisfaction memiliki pengaruh yang signifikan terhadap Customer Loyalty. The results also show that Customer Satisfaction partiallty mediates the effect of Experiential Marketing and Experiential Value on Customer Loyalty.